Addition of phenols compounds to meat dough intended for salami manufacture and its antioxidant effect - Enrico Novelli; Luca Fasolato; Barbara Cardazzo; Lisa Carraro; Agnese Taticchi; Stefania Balzan (Italian Journal of Food Safety, 2014)
A purified extract of phenols compounds (65% of phenolic content of which decarboxymethyl oleuropein aglycone represented 45% of the wet mass) obtained from vegetation water (a by-product of oil mill) was added to a ground meat dough intended for salami manufacture in two concentration levels: 75 and 150 mg/100 g of dough (F1 and F2, respectively). The control batch was composed of lean and fat cuts of pork in 70:30 ratio, 2.7% salt and a mixed starter culture of staphylococci and pediococci. After stuffing into natural casings, salamis were aged until they reached a total weight loss of 30%. The product was then sliced and packaged in a protective atmosphere (nitrogen:carbon dioxide 80:20) and placed in a refrigerator thermostat (2-4°C) with alternating 12 h of artificial light and darkness. The samples were analysed for the measurement of pH, water activity, organic acidity, peroxide number and secondary products of lipid peroxidation at the time of slicing and after 10, 20 and 30 days of storage into the refrigerated thermostat. The pH and water activity were not substantially different between the control and the two enriched batches. The peroxide number and secondary products of lipid peroxidation values in the two batches with phenols were at least substantially lower than the control sample. In conclusion, the phenol compounds obtained from vegetation water have shown no interference with the ripening process while protecting the dough from oxidation.